Three-dimensional dynamic homogenous modeling: The biomechanical influences of leg tissue stiffness on pressure performance of compression biomedical therapeutic textiles - Shi, Yu; Ye, Chongyang; Liu, Rong (Frontiers in Bioengineering and Biotechnology, 2024)
Patient compliance and therapeutic precision of compression textiles (CTs) are frequently limited by the inaccurate pressure distributions along biological bodies in physical-based compression therapy. Therefore, the biomechanical influences of physiological tissue material characteristics of lower extremities on compression generations of CTs need to be explored systematically to improve pressure management efficacy. In this study we developed three-dimensional (3D) homogenous finite element (FE) CT-leg systems to qualitatively compare the pressure diversities along lower limbs with different biomaterial tissue properties under each external compression level.Simultaneously, through the obtained leg circumferential displacement, a contact analysis model was applied to quantitively explore the impact mechanisms of soft leg indentations on the pressure performance of CTs. Based on the experimental validation study, the proposed FE systems could be efficiently utilized for compression performance prediction (error ratio: 7.45%). Through the biomechanical simulation and theoretical calculations, the tissue stiffness characteristics of applied bodies showed significant correlations (p <0.05) with the body circumferential displacements but no correlations (p >0.05) with pressure delivery differences of CTs. This study facilitates the pressure fit design principle and leg mannequin material selection guidance for the development and experimental assessment of CTs. It also provides effective simulation methods for pressure prediction and property parametric optimization of compression materials.